The Translatability Of Puns In Selected Shakespeare’s Sonnets Into Chinese: From The Translator’ Perspectives - Chengzhi, Zhang (2014)
The translatability of pun has been solved in previous studies. The translation strategies of puns can be further explored. The objectives of this study are to examine the translatability of puns, translation strategies of puns. The sources texte of these puns are taken from Ingram & redapth’s (1978) edition of Shakespeare sonnets. The target texts of these puns are taken from the nine corresponding Chinese versions.